Topography of lymph nodes around the right main bronchus - O. I. Fedulov; V. V. Maslyakov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The study is based on the study of 30 organ complexes from the human thoracic cavity, distributed into 5 age groups with 10-year interval, 6 observations in each group: 1st age group – 20–30 years, 2nd age group – 31–40 years, 3rd age group – 41–50 years, 4th age group – 51–60 years, 5th age group – 61–70 years. All medications were taken from people without heart and lung pathology at forensic autopsy according to the generally accepted method. Based on the results obtained, topographic features of lymph nodes location around the right main bronchus are given, which is of practical interest.